Smart Odontogram on Preventive Dentistry: A Managerial and Policy Review at Nala Husada Dental Hospital Surabaya - Indarti, Caecilia; Arya Brahmanta; Rizal, Moh. Basroni; Pinasti, Restika Anindya (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2026)
Background: Digital transformation in dental healthcare has brought forward Smart Odontogram systems that offer structured, electronic, and real-time documentation of dental conditions. This tool is particularly valuable for early detection, monitoring, and prevention of oral diseases. However, its success relies heavily on management readiness and policy. Objective: This study aimed to review the implementation of the Smart Odontogram application from a managerial and policy perspective in supporting preventive dentistry. Methods: This study used a mixed-methods approach. The sample consisted of 12 selected individuals using purposive sampling. Inclusion criterion was involvement in Smart Odontogram implementation for at least six months. Primary data were obtained from interviews and questionnaires, focusing on organizational readiness, human resource competency and training, and managerial challenges and policies. Results: The hospital management has implemented both the hardware and software of Smart Odontogram, but not much (33.3%) integrated with Electronic Medical Record (EMR) system. Only one participant reported a lack of mentoring (8,3%), and only a few received basic training on Smart Odontogram (16,7%). Only one experienced an oversight of data input (8,3%), and a few reported about the lack of quality of data system control (16,7%). Most participants considered Smart Odontogram to be a significant support of preventive dentistry, particularly in the early identification of caries and periodontal diseases (83,3%). Conclusion: The implementation of Smart Odontogram, supported by sound managerial strategies and policies, significantly enhanced preventive dentistry at Nala Husada Dental Hospital.